2000
DOI: 10.1075/pc.8.1.07bau
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing expression from familiar and unfamiliar faces

Abstract: The aim of this study was to clarify the relationship between accessing the identity of a face and making decisions about its expression. Three experiments are reported in which undergraduate subjects made expression decisions about familiar and unfamiliar faces. The decision was slowed either by concealing the mouth region with a black rectangle (experiment 1) or by using a short presentation time (experiments 2 and 3). Results of experiment 1 showed that subjects recognized the displayed expression of celebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 42 publications
1
13
1
Order By: Relevance
“…This applies to both dependent variables: the rate of expected responses and the latency of expected as well as unexpected responses. These results are in agreement with several recent studies about other visually derived semantic codes, namely, emotional expression (Schweinberger et al 1999;Schweinberger and Soukup 1998), facial speech (Schweinberger and Soukup 1998), apparent age (Bruyer et al 1991), and gender (Baudouin et al 2000a(Baudouin et al , 2000bCalder et al 2001;Dehon and Bre¨dart 2001;Dubois et al 1999;Ganel and Goshen-Gottstein 2002;Goshen-Gottstein and Ganel 2000;O'Toole et al 1996;Rossion 2002). Moreover, in the nine cases, the performance improved when the familiarity of the morphs increased, as the linear component was significant every time.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This applies to both dependent variables: the rate of expected responses and the latency of expected as well as unexpected responses. These results are in agreement with several recent studies about other visually derived semantic codes, namely, emotional expression (Schweinberger et al 1999;Schweinberger and Soukup 1998), facial speech (Schweinberger and Soukup 1998), apparent age (Bruyer et al 1991), and gender (Baudouin et al 2000a(Baudouin et al , 2000bCalder et al 2001;Dehon and Bre¨dart 2001;Dubois et al 1999;Ganel and Goshen-Gottstein 2002;Goshen-Gottstein and Ganel 2000;O'Toole et al 1996;Rossion 2002). Moreover, in the nine cases, the performance improved when the familiarity of the morphs increased, as the linear component was significant every time.…”
Section: Discussionsupporting
confidence: 91%
“…The same conclusion was reached by Schweinberger et al (1999) for identity and emotional expression, and by Bruyer et al (1991) for familiarity and age of faces. Also, Ganel and Goshen-Gottstein (2002) reported results indicating that gender and identity are not processed independently from each other, and this non-independence is supported by other behavioural studies (Baudouin et al 2000a(Baudouin et al , 2000bDehon and Bre¨dart 2001;Goshen-Gottstein and Ganel 2000;O'Toole et al 1996;Rossion 2002), functional neuroimaging studies (Dubois et al 1999;Rossion et al 2001), and statistical analysis of the pixel intensity of the images (Calder et al 2001).…”
mentioning
confidence: 70%
“…However, given the fact that the images were taken from a pool that was used for publication in print media that are widely read in the area in which our participants were resident, these data support the idea that our participants had encountered celebrities more often with neutral and moderately happy expressions than with other expressions. better for smiling faces) has been raised in a few publications that are not frequently accessible to researchers in face perception (Endo et al 1992;Kottoor 1989;Sansone and Tiberghien 1994) all cited in Baudouin et al (2000b). In addition, one study (Baudouin et al 2000a) reported an effect of smiles on familiarity ratings for both familiar and unfamiliar faces.…”
Section: Discussionmentioning
confidence: 99%
“…The second issue is whether a happy expression would be a confounding factor influencing unfamiliar identity recognition, as suggested in several studies on familiar faces (e.g., Baudouin et al, 2000 ). To examine this issue, mean reaction times in the filtering block in four experiments were subjected to a RM-ANOVA with discriminability as the between-subject variable and categories of expression as the within-subject variable.…”
Section: Methodsmentioning
confidence: 99%